Respostas

2013-11-28T16:32:59-02:00
A) f ( 2 ) = ( 2 ) ² - 2 .2 - 3                  c) f ( - 1 ) = ( - 1 ) ² - 2 . ( - 1 ) - 3 
f( 2 ) = 4 - 4 - 3                                    f ( - 1 ) = 1 + 2 - 3
f( 2 ) = - 3                                           f( - 1 ) = 0

b) f ( 0 ) = ( 0 ) ² - 2 . 0 - 3                   d ) f ( 5 ) = ( 5 )² - 2 . 5 - 3
   f ( 0 ) = 0 - 0 - 3                                    f ( 5 ) = 25 - 10 - 3
   f ( 0 ) = - 3                                           f ( 5 ) = 12

1 5 1